3(x-1)+4(1-2x)=8-6x

Simple and best practice solution for 3(x-1)+4(1-2x)=8-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-1)+4(1-2x)=8-6x equation:


Simplifying
3(x + -1) + 4(1 + -2x) = 8 + -6x

Reorder the terms:
3(-1 + x) + 4(1 + -2x) = 8 + -6x
(-1 * 3 + x * 3) + 4(1 + -2x) = 8 + -6x
(-3 + 3x) + 4(1 + -2x) = 8 + -6x
-3 + 3x + (1 * 4 + -2x * 4) = 8 + -6x
-3 + 3x + (4 + -8x) = 8 + -6x

Reorder the terms:
-3 + 4 + 3x + -8x = 8 + -6x

Combine like terms: -3 + 4 = 1
1 + 3x + -8x = 8 + -6x

Combine like terms: 3x + -8x = -5x
1 + -5x = 8 + -6x

Solving
1 + -5x = 8 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
1 + -5x + 6x = 8 + -6x + 6x

Combine like terms: -5x + 6x = 1x
1 + 1x = 8 + -6x + 6x

Combine like terms: -6x + 6x = 0
1 + 1x = 8 + 0
1 + 1x = 8

Add '-1' to each side of the equation.
1 + -1 + 1x = 8 + -1

Combine like terms: 1 + -1 = 0
0 + 1x = 8 + -1
1x = 8 + -1

Combine like terms: 8 + -1 = 7
1x = 7

Divide each side by '1'.
x = 7

Simplifying
x = 7

See similar equations:

| a=bq+r | | m^2-2m-10=0 | | log(5)(2x-9)=1 | | 1/x^-8(x^9) | | (x^((sin(x))^x)-sin(x^(x^sin(x))))/x^3 | | x=163+(-1.3)*99 | | 3.7/2=x/9 | | (-1/4)3 | | 27=3c-9-6c | | 3v^2+100v-5700=0 | | y^2+7y=12 | | 2w^2-11w-6=0 | | x^2=32x+240 | | 4z+20=32 | | .20=in(y) | | -10x=5-10x | | 15d^2/c^2 | | 2.0=log(x) | | 5x^4-8x^3-3x^2=0 | | p(x)=5-10x | | (2/x-2)=(x/x^2-8) | | 3(8-x)=6x+15 | | 0=35+9.8x | | 0.18y+0.07(y+4000)=280 | | -300+3Q=Q^2 | | cx+hy=jx | | xc+hy=j | | 1052=X*(3.6/5)*70 | | 8k+7=6k+19 | | 2(x-5)+1=3(x-1)+5 | | 1052=X*(3.6/5)*Y | | 4(5x-3)=x+7 |

Equations solver categories